Effectiveness of Organizational Communication in Distribution of Village Funds to the Community in Air Joman District, Asahan Regency - Khualid Armansyah Lubis (UMSU, 2023)
This study aims to explain the organizational communication mechanisms that occur in two state institutions, namely sub-districts and villages in the management of village funds in Air Joman sub-district, Asahan district. This study uses a qualitative approach, data is collected using several methods, namely direct observation of objects research, interviews with informants determined purposively, including six village heads and village heads in the Air Joman sub-district, Asahan Regency, community members and employees in the Air Joman sub-district government. Researchers also reviewed several documents relevant to the study theme. Both documents sourced from villages, sub-districts and through digital tracing. The research results show that organizational communication at the sub-district level occurs up to down, where the sub-district head and the sub-district secretary have a big role in distributing information. Communication within the scope of duties and discussions regarding work issues are carried out in a formal atmosphere. Organizational communication is considered effective if organizational members do what they have been told in the meeting, not based on feedback between the parties involved